Mangrove Optimization to Improve Economic Growth Of Coastal Communities - Siregar, Pramiado Samuel; Farista, Dian; Fausi, Ria Risti (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
Mangrove leaves contain high antioxidants that can be used as drinks such as tea. This research aims to make de.ruju tea, which is a tea that is produced simply. The research methods include organoleptic tests to determine the level of public liking for de.ruju tea. besides that, SWOT analysis to determine the strengths, weaknesses, opportunities and threats to determine the opportunity value of de.ruju products. The results showed that processing mangrove leaf raw materials into functional food as tea improved the economic level of the Tambakrejo Village community by increasing profits by 112%. The SWOT analysis results show that de.ruju products have an IFAS matrix value of 2.7. This shows that the product situation is very good and has advantages higher than weaknesses and an EFAS matrix of 2 so that the product is able to take advantage of opportunities to avoid threats from the environment.